Grid Modernization Policies in California: Coherence of Policy Goals - Amponsem, Josephine (European Scientific Journal, ESJ, 2026)
In grid modernization, California stands out. To that end, this research explores the role of policy coherence in the success story of California. It avers that policy coherence is only a contributive factor to California’s success in grid modernization, as other factors like political will, regulatory capacity, technology, and stakeholder collaboration played a more significant role than policy coherence did. The study demonstrates that for California to have had exceptional success amidst the overall low policy coherence, the other factors mattered more in the process. A large number of smart meters are found in California, which improve grid responsiveness and user engagement through precise collection of data on energy usage patterns. Besides, they increase the integration of renewable energy sources, and improve effective resource management. In conclusion, California contributes enormously to the overall reliability and resilience of grid modernization in the US. Stakeholders should collaboratively ensure increased policy coherence in grid modernization, and increased adoption, utilization, and sustenance of smart technologies and deliverables.